Use of Farmers’ Portal for dissemination of oil palm agro-management technology in India - Rani, K.L. Mary; Prasad, M.V.; Arulraj, S.; Mounica, B. (Journal of Plantation Crops, 2015)
In India, mobile phones are widely used for effective communication of various agro-management information to farmers. Oil palm is cultivated in India since two decades under irrigated conditions. The crop being new, farming technology has to be disseminated to field extension staff, growers and developers to take quick and apt decisions. Farmers’ Portal launched by Government of India (GOI) for farming community is also being used to disseminate the oil palm farming technology to its stakeholders through short message services (SMS). Contents prepared on various aspects on oil palm cultivation were published as text SMS (568) to the unique mobile numbers (19,301) of stakeholders of oil palm in India. Messages were published in four languages viz., Hindi, English, Telugu and Kannada to reach the stakeholders in vernacular languages. Stakeholders contact the Institute, seeking more information on various farming practices of oil palm viz., planting, protection, general information, fertilizer application, irrigation, harvesting etc. Consultation was provided to 304 farmers who sought information on fertilizer management (34.2%) followed by crop protection aspects (28.3%) and general information (24.0%) on oil palm cultivation. Feedback received from farmers showed that the SMS contents were useful in the following order: irrigation (15%), fertilizer application (14%), disease management (8%), weed control (4%) and all messages were useful (59%). Majority of the farmers (68%) perceived the messages were relevant to their crop growth/stages and 33 per cent farmers were adopting the practices sent through SMS.